Physics and Radiobiology of Nuclear Medicine - Saha, Gopal B.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
The Fourth Edition of Dr. Gopal B. Saha’s Physics and Radiobiology of Nuclear Medicine was prompted by the need to provide up-to-date information to keep pace with the perpetual growth and improvement in the instrumentation and techniques employed in nuclear medicine since the last edition published in 2006. Like previous editions, the book is intended for radiology and nuclear medicine residents to prepare for the American Board of Nuclear Medicine, American Board of Radiology, and American Board of Science in Nuclear Medicine examinations, all of which require a strong physics background. Additionally, the book will serve as a textbook on nuclear medicine physics for nuclear medicine technologists taking the Nuclear Medicine Technology Certification Board examination. The Fourth Edition includes new or expanded sections and information for: * PET/MR, including the attenuation correction method and its quality control tests; * accreditation of nuclear medicine and PET facilities; * solid state digital cameras; * time of flight and scatter correction techniques; * CT scanners and attenuation correction in SPECT/CT; * partial volume effects; * quality control of CT scanners; * ion chamber survey meters, proportional counters, and G-M counters.
Structure of Matter -- Radioactive Decay -- Kinetics of Radioactive Decay -- Statistics of Radiation Counting -- Production of Radionuclides -- Interaction of Radiation with Matter -- Gas-Filled Detectors -- Scintillation and Semiconductor Detectors -- Gamma Cameras -- Performance Parameters of Gamma Cameras -- Digital Computers in Nuclear Medicine -- Single Photon Emission Computed Tomography -- Position Emission Tomography -- Internal Radiation Dosimetry -- Radiation Biology -- Radiation Regulations and Protection -- Appendix A -- Appendix B -- Appendix C.
Keywords: Nuclear medicine; Radiology; Radiotherapy; Nuclear Medicine; Imaging / Radiology; Diagnostic Radiology; Radiotherapy